Synthesis and Characterization of Some Lanthanide(III) Chelates of Phenyl Thiosemicarbazones - RAJENDRAN, G.; AMITHA, V. (Asian Journal of Chemistry, 2010)
A series of nine complexes of lanthanide(III) ion with salicylaldehyde N(4)-phenylthiosemicarbazone (SPT) and various anions were synthesized and characterized. From spectral investigations along with elemental analysis, conductance and magnetic measurements, the general formula of the complexes were assigned to be [Ln(SPT)2X] (where Ln = La(III), Pr(III) or Nd(III), X = NO3–, NCS– and ClO4–, SPT = salicylaldehyde N(4)-phenylthiosemicarbazone. Thermal stabilities of complexes were sttudied from TG and DTG curves.